What a Rich BIOTROP: Development Database Framework of Biodiversity Heritage Collections - Harry Imantho; Saeful Bachri; Ina Retnowati; Sri Sudarmiyati Tjitrosoedirdjo; Soekisman Tjitrosemito; Sri Widayanti; Risa Rosita; Irawan Irawan; Supriyanto Supriyanto; Iman Hidayat (SEAMEO BIOTROP, 2023)
The need for biodiversity science with the availability and interoperability of data on the internet reinforces each other. This is driven by the increasing literacy of the world community regarding the impact of loss of biodiversity on the sustainability of human life. High-quality biodiversity data is needed to demonstrate that spatio-temporal loss of biodiversity has led to a reduction in quality of life. This facts have underpinned SEAMEO BIOTROP to increase the visibility of managed biodiversity collection data. SEAMEO BIOTROP maintains thousands of valuable herbarium collections of weeds, trees and invasive plants; fungi, insects and pests for research and testing purposes. These historic and valuable collections of biodiversity need to be preserved and better managed in digital format so that the information is available to botanists and the general public around the world. A study regarding the development of an integrated biodiversity collection database framework has been carried out by SEAMEO BIOTROP. This study aims to formulate and develop an initial framework for the BIOTROP biodiversity database that is relevant to national, regional and global needs. This study succeeded in developing an integrated database framework that brings together all digital data from the SEAMEO BIOTROP biodiversity collection into a database management system. This database management system also adopts Darwin Core metadata to ensure easy exchange and sharing of data with existing biodiversity data management systems in the world.